(3GdYbO GdePgH aj WHbGJ MedI GdePgHs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s ((3YHOGddg Hf eMeO GdfTGFi s)
(3ChdgG (B:s
(3hHYO agPg MedI egdg ai eYQaI WHbGJ GdTGaYjg s
(3GfXQ GdbSe GdChd HQbe (B337 (3hGdbSe GdKGfi HQbe (B739s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B297s
Keywords: (3GdJGQjNs